Ownership Status of Implementation of Assets in Mixed Marriages - Rohman, Bintang Nur; Mukhoyyaroh, Vina Durrotul; Arifin, Adelia Arnanda (Contemporary Issues on Interfaith Law and Society, 2023)
The division of assets is often the main problem in divorce cases. It's like a treasure trove that becomes a problem for both parties. This article discusses the status of ownership of fixed objects on the division of assets in mixed marriages. By using research that is qualitative in nature and sourced from the law as a primary source and research results as a secondary source of law. The author describes the findings and discussion in this article. Which marriage can also result in the complete absence of gono gini property but the husband's property remains the husband's property and the wife's property also remains the wife's property. The division of assets by types of fixed objects in arbitrary assets is also one of the main issues that becomes a problem.